Analysis of the Behavior of Deep Eutectic Solvents upon Addition of Water: Its Effects over a Catalytic Reaction - Campodónico, Paola; Alarcón, Jazmín; Alcázar, Jackson; Olivares, Belén; Suárez, Cristian (Molecules, 2024)
This study presents the potential role of deep eutectic solvents (DESs) in a lipase-catalyzed hydrolysis reaction as a co-solvent in an aqueous solution given by a phosphate buffer. Ammonium salts, such as choline chloride, were paired with hydrogen bond donors, such as urea, 1,2,3-propanetriol, and 1,2 propanediol. The hydrolysis of p-nitrophenyl laureate was carried out with the lipase Candida antarctica Lipase B (CALB) as a reaction model to evaluate the solvent effect and tested in different DES/buffer phosphate mixtures at different % w/w. The results showed that two mixtures of different DES at 25 % w/w were the most promising solvents, as this percentage enhanced the activities of CALB, as evidenced by its higher catalytic efficiency (kcatKM). The solvent analysis shows that the enzymatic reaction requires a reaction media rich in water molecules to enable hydrogen-bond formation from the reaction media toward the enzymatic reaction, suggesting a better interaction between the substrate and the enzyme-active site. This interaction could be attributed to high degrees of freedom influencing the enzyme conformation given by the reaction media, suggesting that CALB acquires a more restrictive structure in the presence of DES or the stabilized network given by the hydrogen bond from water molecules in the mixture improves the enzymatic activity, conferring conformational stability by solvent effects. This study offers a promising approach for applications and further perspectives on genuinely green industrial solvents. Versión Publicada